Parental Involvement and Executive Function in Emerging Adults with Type 1 Diabetes. (16th May 2019) - Berg, Cynthia A; Wiebe, Deborah J; Lee Tracy, Eunjin; Kelly, Caitlin S; Mello, Daniel; Turner, Sara L; Butner, Jonathan E; Munion, Ascher K; Mansfield, Jessica H; White, Perrin C; Murray, Mary; Suchy, Yana
Abstract: Objective: To examine (a) changes in parental involvement across early emerging adulthood, (b) whether yearly fluctuations in parental involvement were associated with adherence and glycated hemoglobin (HbA1c) over time, and (c) whether higher involvement was more beneficial for those with poorer executive function (EF). Methods: A total of 228 high school seniors ( M age = 17.76) with type 1 diabetes reported on mothers' and fathers' acceptance, knowledge of diabetes activities, disclosure to mothers and fathers regarding diabetes, and adherence at four yearly time points. At baseline, participants completed performance-based measures of EF. HbA1c was collected from assay kits. Results: Growth curve models revealed significant declines in disclosure to fathers and mothers' and fathers' knowledge of diabetes activities; no changes were found in mothers' or fathers' acceptance nor disclosure to mothers. Multilevel models indicated significant between-person effects for nearly all aspects of parental involvement with more acceptance, knowledge, and disclosure associated with better HbA1c and adherence. Within-person effects for disclosure to fathers, and mothers' and fathers' knowledge indicated that in years when emerging adults perceived higher amounts of these types of involvement (compared with their own average), HbA1c was lower. Within-person effects were found for acceptance to mothers, disclosure to mothers and fathers, and mothers' diabetes knowledge for adherence. Disclosure to fathers and mothers' knowledge of diabetes activities were especially beneficial for HbA1c for those with poorer EF performance. Conclusions: Parental involvement in diabetes management remains important during the high-risk time of emerging adulthood, especially for those with poorer EF.